Multiwavelength operation in praseodymium fiber laser using polarization maintaining fiber and nonlinear polarization rotation in ring cavity - Ahmad, Harith; Ahmed, Mahmoud Hazzaa Mohammed (Society of Photo-optical Instrumentation Engineers (SPIE), 2019)
A multiwavelength praseodymium fiber laser (MWPFL) operating at the 1300-nm region is proposed and demonstrated. The MWPFL incorporates a polarization maintaining fiber acting as a Lyot birefringence filter, and when combined with the nonlinear polarization rotation effect, generates the desired multiwavelength output. Careful adjustment of the polarization controller at different angles allows for the generation of up to five channels above a power level of -3.4 dBm and a spacing of 0.2 nm. The peak power fluctuation and wavelength shifts of these lasers are measured to be less than 2.1 dB and 0.04 nm, respectively, over an observation period of 60 min. The demonstrated MWPFL shows good stability combined with a simple structure for generating a multiwavelength output at the 1300-nm wavelength region. © 2019 Society of Photo-Optical Instrumentation Engineers (SPIE).